Revitalization of a Futuristic Smart Bus Station: K.H. Ahmad Sanusi Sukabumi - Muhamad Andika Nugroho; Anung B. Studyanto (Faculty Of Arts and Design Sebelas Maret University, 2025)
Along with the increasing population growth every year which has a variety of economic and social activities, it causes an increasing demand for development, repair, and improvement of infrastructure and services that support the increasing mobility of the population. One of the important roles in supporting the movement of population mobility is the terminal. As an effort to support the smooth mobility of the population, a terminal is needed that is feasible and able to adjust its carrying capacity to the development of the surrounding area. Type A Bus Terminal K.H. Ahmad Sanusi Sukabumi City is the only bus terminal in Sukabumi City. The K.H. Ahmad Sanusi Sukabumi Terminal is a vital infrastructure for the transportation system in Sukabumi City and plays an important role in the mobility of the population and economic development of the region. However, this terminal is still not less feasible as a type A terminal and still has several other problems such as flow problems that make the circulation of people and goods unclear and the division of zones in the terminal which is still not firm, as well as the lack of cleanliness and comfort in the terminal so that improvement efforts are needed to ensure that the K.H. Ahmad Sanusi Sukabumi Terminal is able to serve and support various activities in it Optimal. Therefore, to overcome all the problems that exist in the K.H. Ahmad Sanusi Sukabumi Bus Terminal and in line with the development of increasingly modern technology, applying the concept of smart bus station to the K.H. Ahmad Sanusi Sukabumi Bus Terminal is very relevant. In addition to being able to overcome the problems found in the K.H. Ahamad Sanusi Sukabumi Bus Terminal, the implementation of smart bus stations can support economic and creative growth. Keywords : Sukabumi, Terminal, Smart bus station